Defining the impact of paternal diet on maternal cardiometabolic ill-health in late gestation - Khoshkerdar, Afsaneh (2024)
It is well-established that poor maternal nutrition prior to, or during, pregnancy can have a range of adverse consequences for the health of the mother and her offspring. For the mother, these consequences can become manifest in an increased risk of developing conditions such as preeclampsia and gestational diabetes. For her offspring, studies have shown an increased predisposition towards a series of non-communicable diseases including obesity, type-2 diabetes, and cardiovascular disease. Such connections between maternal health and offspring well-being have been defined over recent decades through the detailed examination of human epidemiological cohorts as well as a multitude of animal models.